Individual goal‐oriented cognitive rehabilitation to improve everyday functioning for people with early‐stage dementia: A multicentre randomised controlled trial (the GREAT trial). (1st March 2019) - Clare, Linda; Kudlicka, Aleksandra; Oyebode, Jan R.; Jones, Roy W.; Bayer, Antony; Leroi, Iracema; Kopelman, Michael; James, Ian A.; Culverwell, Alison; Pool, Jackie; Brand, Andrew; Henderson, Catherine; et al.
Abstract : Objectives: To determine whether individual goal‐oriented cognitive rehabilitation (CR) improves everyday functioning for people with mild‐to‐moderate dementia. Design and methods: Parallel group multicentre single‐blind randomised controlled trial (RCT) comparing CR added to usual treatment (CR) with usual treatment alone (TAU) for people with an ICD‐10 diagnosis of Alzheimer, vascular or mixed dementia, and mild‐to‐moderate cognitive impairment (Mini‐Mental State Examination [MMSE] score ≥ 18), and with a family member willing to contribute. Participants allocated to CR received 10 weekly sessions over 3 months and four maintenance sessions over 6 months. Participants were followed up 3 and 9 months post randomisation by blinded researchers. The primary outcome was self‐reported goal attainment at 3 months. Secondary outcomes at 3 and 9 months included informant‐reported goal attainment, quality of life, mood, self‐efficacy, and cognition and study partner stress and quality of life. Results: We randomised (1:1) 475 people with dementia; 445 (CR = 281) were included in the intention to treat analysis at 3 months and 426 (CR = 208) at 9 months. At 3 months, there were statistically significant large positive effects for participant‐rated goal attainment (d = 0.97; 95% CI, 0.75‐1.19), corroborated by informant ratings (d = 1.11; 95% CI, 0.89‐1.34). These effects were maintained at 9 months for both participant (d = 0.94; 95% CI, 0.71‐1.17) and informant (d = 0.96; 95% CI, 0.73‐1.2) ratings. The observed gains related to goals directly targeted in the therapy. There were no significant differences in secondary outcomes. Conclusions: CR enables people with early‐stage dementia to improve their everyday functioning in relation to individual goals targeted in the therapy.